1988
DOI: 10.1038/bjc.1988.96
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary tumours in women with vulvar neoplasms: a case-control study

Abstract: Summary We sought to determine whether women with in situ or invasive squamous cell vulvar cancer were more likely than other women to have had a previous or concurrent tumour at other anogenital sites. One hundred and fifty-eight women with vulvar cancer were identified who were first diagnosed during 1980-1985, were ages 18-79 years at that time, and were residents of one of three counties in western Washington. Two control groups were selected: (1) from records of hospital pathology departments, a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The most frequently affected sites were the labia majora (47), the labia minora (23), and the posterior fourchette (22). Other affected sites were the clitorus (5), mons pubis (1), perineal (14), and perianal (3) areas. Thirteen (76.5%) of the 17 patients with perineal and perianal disease had multifocal disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently affected sites were the labia majora (47), the labia minora (23), and the posterior fourchette (22). Other affected sites were the clitorus (5), mons pubis (1), perineal (14), and perianal (3) areas. Thirteen (76.5%) of the 17 patients with perineal and perianal disease had multifocal disease.…”
Section: Resultsmentioning
confidence: 99%
“…Husseinzadeh (11) reported an incidence of 35% when coexisting or preexisting condylomata was the objective criterion used, while in a more recent study polymerase chain amplification techniques confirmed HPV in 72% of cases (12) . The role of HPV in multifocal VIN 3, more often symptomatic, and in the multicentricity of other neoplastic lesions on the lower genital tract has been established (13) and emphasizes the need for concomitant cervical, vaginal, and anal examination, preferably by colposcopy, in the evaluation and follow-up of these women (14,15) . As the natural history of the disease has become more clearly defined, extensive and potentially mutilating surgery has little place in the contemporary management of VIN 3, except in extensive multifocal disease (5) .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, about 20% of vulvar cancers are associated with other primary malignancies of the cervix or vagina [25,28]. These studies suggest that the coexistence of several pathologic entities may reflect a common etiology or 'field effect' in these lesions, which is likely to be a sexually transmitted disease, and in the majority of cases, HPV infection [25][26][27]. In several reported cases, basaloid or warty types of VIN were found adjacent to invasive vulvar carcinoma of similar types [20].…”
Section: Yang/gordonmentioning
confidence: 99%
“…Indeed, several studies have indicated that patients with vulvar neoplasms are at increased risk of developing multiple genital malignancies, synchronously or metachronously, at some time during life [25][26][27]. In fact, about 20% of vulvar cancers are associated with other primary malignancies of the cervix or vagina [25,28].…”
Section: Yang/gordonmentioning
confidence: 99%
See 1 more Smart Citation